Organophosphorus compounds and oximes: a critical review - Worek, Franz (Arch Toxicol, 2020)
Organophosphorus (OP) pesticides and nerve agents still pose a threat to the population. Treatment of OP poisoning is an ongoing challenge and burden for medical services. Standard drug treatment consists of atropine and an oxime as reactivator of OP-inhibited acetylcholinesterase and is virtually unchanged since more than six decades. Established oximes, i.e. pralidoxime, obidoxime, TMB-4, HI-6 and MMB-4, are of insufficient effectiveness in some poisonings and often cover only a limited spectrum of the different nerve agents and pesticides. Moreover, the value of oximes in human OP pesticide poisoning is still disputed. Long-lasting research efforts resulted in the preparation of countless experimental oximes, and more recently non-oxime reactivators, intended to replace or supplement the established and licensed oximes. The progress of this development is slow and none of the novel compounds appears to be suitable for transfer into advanced development or into clinical use. This situation calls for a critical analysis of the value of oximes as mainstay of treatment as well as the potential and limitations of established and novel reactivators. Requirements for a straightforward identification of superior reactivators and their development to licensed drugs need to be addressed as well as options for interim solutions as a chance to improve the therapy of OP poisoning in a foreseeable time frame.